Development of academic communication skills for students in its first year of teaching initial training (Revista Electrónica Diálogos Educativos. REDE, 2017)
Reading and writing strategies are used primarily in the academic field because of their clear impact on learning processes. Hence, in teacher training, it is necessary for the university teacher to develop academic reading and writing strategies, as an essential resource for the construction of disciplinary learning, which is part of academic literacy.Under this precedent, he realizes an innovation, which is situated in a first-year subject, which is common to all the PedagogyÂ careers of the Metropolitan University of Education Sciences, whose purpose is to develop in students the ability to organize the information that characterize the discursive genres of specialized areas in the area of Education and Pedagogy.The strategies are intentional, which is a key factor that places the student in an active perspective against the communicative process.The learning evidenced in the development of the experience emphasizes fields of academic integration, thus opening a door for the development of necessary competences such as analysis, problem solving and critical thinking of Pedagogy students.